Análisis de Vulnerabilidades a los Sistemas Informáticos de la Empresa Ingenio Azucarero del Norte de Compañía de Economía Mixta “IANCEM” Basado en la Metodología OWASP - Guerra Olmedo, Diego Fernando (2025)
In today's business landscape, characterized by an increasing dependence on technology, companies in the productive sector face unprecedented cybersecurity challenges. IANCEM, a leading sugar trading company in northern Ecuador, is no exception to this reality. Despite having recently modernized its facilities to optimize production and comply with rigorous environmental standards, IANCEM is in a vulnerable position when it comes to the security of its web systems. This investigation arises from the critical need to assess and strengthen IANCEM's security posture in the digital environment. Although the company has implemented security measures on its web systems, these have not been subjected to thorough validation to determine their effectiveness against the increasing sophistication of cyberattacks. This gap in validation represents a significant risk to data integrity, operational continuity, and ultimately the company's reputation in an increasingly competitive and security-conscious market. The main objective of this study is to perform a comprehensive and meticulous analysis of IANCEM web systems, using the OWASP (Open Web Application Security Project) methodology as a reference framework. This methodological choice is not arbitrary\; OWASP has established itself as a de facto standard in the IT security industry, offering a structured and up-to-date approach to the identification, assessment and mitigation of security risks in web applications. The analysis will focus on the detection and assessment of a wide range of potential vulnerabilities, with special emphasis on those that have proven to be particularly critical in similar business environments.